2010
DOI: 10.1590/s0104-530x2010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Maturidade em gestão de projetos em pequenas empresas desenvolvedoras de software do Polo de Alta Tecnologia de São Carlos

Abstract: Este artigo analisa o nível de maturidade em gestão de projetos de pequenas empresas desenvolvedoras de software, pertencentes ao polo tecnológico de São Carlos. Por meio de estudo de casos múltiplos, de caráter exploratório-descritivo, descrevem-se o grau de maturidade em gestão de projetos das empresas, suas práticas e problemas enfrentados. Foram analisadas cinco (5) empresas e os resultados indicam estágios iniciais de maturidade em gestão de projetos, baixos níveis de formalização das atividades, ausência… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…They are recent publications, after 2009, which supports the previous hypothesis that research on technology companies is a trend. Brazilian SMEs presented high levels of informality and a lack of knowledge and risk management (Juca et al, 2010;Miranda et al, 2014). The researches were performed in a qualitative way, demonstrating that the area is still in development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They are recent publications, after 2009, which supports the previous hypothesis that research on technology companies is a trend. Brazilian SMEs presented high levels of informality and a lack of knowledge and risk management (Juca et al, 2010;Miranda et al, 2014). The researches were performed in a qualitative way, demonstrating that the area is still in development.…”
Section: Discussionmentioning
confidence: 99%
“…The researches were performed in a qualitative way, demonstrating that the area is still in development. The themes were: project management maturity (Juca et al, 2010); risk management (Miranda et al, 2014); PMO implementation (Richter, 2009); and the development of software that could help SMEs to improve their practices (Pereira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jucá Jr., Conforto and Amaral (2010) studied software developer companies under the focus of CMMI (Capability Maturity Model Integration) and concluded that this standard is not appropriate to analyze NPD practices in small businesses. Da Silva, Mello, Siqueira, Godoy and Salgado (2010) discuss the risk management techniques application in auto parts companies.…”
Section: Project Management Offices In New Product Developmentmentioning
confidence: 99%